Model Role Playing Berorientasi Kearifan Lokal Cupak Gerantang Berbantuan AI Sebagai Upaya Revitalisasi Nilai Karakter di Sekolah Dasar - Rusyada, Gozin Najah; Dewi, Nurul Kemala; Tahir, Muhammad; Hidayat, Irfan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop a Cupak Gerantang-based learning model utilizing Role Playing and Artificial Intelligence (AI) as a medium to strengthen character education based on Sasak local wisdom. This development is expected to become a pedagogical innovation that integrates cultural values, technology, and active learning methods. This study uses a Research and Development (R&D) approach with three main stages: (1) preliminary stage, (2) prototyping stage, and (3) assessment. The research subjects consist of two experts, one classroom teacher, and 20 students from SD Negeri 1 Jenggala, North Lombok Regency. Data were collected through observation, interviews, expert validation, and student response questionnaires, which were analyzed descriptively both qualitatively and quantitatively. The results of the study indicate that the learning model has a very high validity level, with an average score of 3.65 from media experts and 3.66 from learning experts. Limited trials showed practical categorization, with an average score of 3.45, covering aspects of ease of implementation, clarity of learning steps, and the attractiveness of AI-based animated media. Teachers and students gave a positive response to the integration of Cupak Gerantang digital animation equipped with AI voice-over features, as it was considered to enhance interactivity and understanding of moral values.